S89 Ex vivo studies of the gal-3-fibrosome hypothesis in IPF and non-fibrotic control lung tissue and myofibroblasts. (12th November 2019) - Miah, A; Stylianou, P; Tongue, P; Roach, K; Bradding, P; Gooptu, B
Abstract : Background: Galectin-3 critically mediates experimental fibrosis, potentiating pro-fibrotic effects of transforming growth factor (TGF)-β1, and is highly expressed in idiopathic pulmonary fibrosis (IPF). Therefore, a galectin-3 small molecule glycomimetic antagonist is in Phase 2B trials. Galectin-3 may mediate pathogenesis in alveolar epithelial cells (AECs) and myofibroblasts by nucleating a macromolecular complex assembly on the cell surface. We term this the 'gal-3-fibrosome'. In addition to galectin-3, putative components include CD98:β1-integrin complex and TGF-β receptor II (TGF-βRII). Through multiple experimental techniques, we have established evidence for the gal-3-fibrosome hypothesis in AECs. Aim: Characterise mRNA and protein levels and co-localisation of galectin-3 with CD98:β1-integrin and TGF-βRII, basally and with pro-fibrotic stimulation in non-fibrotic control (NFC) and IPF contexts ex vivo . Methods: We studied the expression levels of galectin-3, CD98 heavy chain (CD98hc) and β1-integrin at mRNA and protein levels, and their co-localisation. We characterised lung tissue and low passage IPF and NFC lung myofibroblasts (passage 4–5), basally and with TGF-β1 stimulation. Results: IPF lung tissue stained positively for galectin-3, β1-integrin and CD98 but NFC lung tissue did not. TGF-β1 treatments increased mRNA levels for transcripts of β1-integrin and CD98hc, but not galectin-3 in human lung tissue cultured ex vivo . More pronounced differential responses were detected at the protein level in lung myofibroblasts purified ex vivo : protein levels of β1-integrin and CD98hc increased, whilst galectin-3 levels dropped. There was a concomitant decrease in galectin-3 co-localisation with β1-integrin and CD98hc in NFC lung myofibroblasts. However, no alteration in co-localisation was observed in IPF-derived lung myofibroblasts. Conclusion: Putative gal-3-fibrosome components co-localise at the cellular level in IPF lung tissue. Co-localisation is also evident in IPF lung myofibroblasts purified ex vivo . Our data indicate this is mediated by increased transcription of mRNA encoding CD98hc and β1-integrin but that observed galectin-3 increases are more likely related to stabilisation at the protein level. Our unexpected findings regarding reductions in galectin-3 levels with TGF-β1 treatment in human NFC lung tissue and myofibroblasts ex vivo are consistent with a negative feedback loop restricting gal-3-fibrosome formation. This may then be counteracted by increased gal-3-fibrosome stabilisation in IPF to enhance pathogenic TGF-β1 signalling.